(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
With exceptions, the correlation between relative energies of isomers and their relative abundances in the interstellar medium (ISM) holds to an extent. Among the C2H6O2 isomers, ethylene glycol is the only known interstellar isomer but there is no report regarding the astronomical searches for ethane 1,1-ethanediol (the most stable isomer of the group) due to lack of spectroscopic and other parameters that would have warranted the search. In this article, the most energetically stable conformer of 1,1-ethanediol was investigated, its spectroscopic, and other parameters are obtained from high level ab initio quantum chemical methods. Accurate spectroscopic parameters are obtained at the CCSD(T) level. The proposed formation route of ethane 1,1-diol has a surmountable barrier considering the nature/abundance of the participating species and the energy sources in ISM. The astrophysical implications of these results are discussed and the astronomical searches of ethene 1, 1 diol are proposed.